109 Game Changing Magnetic Experience in Rural and Urban Wirral Peninsula - Our Experience with Magseed Localisation of Impalpable Breast Tumours and Axillary Nodes. (4th May 2021) - Arif, T; Vinayagam, R; Lund, J M; Poonawala, S
Abstract: Introduction: Magseed is a novel localization technology in which a tiny seed is inserted to accurately mark the site of breast tumour. These can be detected intra-operatively by sentimag localization system. It aids localization of impalpable breast lesions improving margin clearance rates. Method: A prospective study of first fifty Magseed localised breast tumour and axillary node excisions in Clatterbridge General Hospital. Results: A total of 50 patients had 52 Magseed inserted. n = 14 was symptomatic, n = 35 was screen detected and n = 1 was an incidental finding on surveillance mammogram for a B3 lesion. 30 seeds were inserted on the right and 22 were inserted on the left (two were bilateral). 44 seeds were inserted under ultrasound guidance and the rest were targeted under stereo guidance (n = 8). Deployment of two resulted in malposition requiring wire localization. Mean age of subjects was 59.76 (range 31-81) years. Mean time to surgery after magseed insertion was 8.04 (range 1-27) days. Mean weight of the specimen was 48.57(range 10-264) gm. Mean size of the lesions was 20.32 (range 8-65) mm. Redo surgery for margin clearance was performed bringing the re-excision rate to 15.38% (n = 8). Conclusions: We conclude that Magseed localization of breast tumours is a safe and reliable technique